Turning the worm: the eradication of Guinea worm disease in west Africa - Cairncross, Sandy (Henry Stewart Talks, 2011)
Natural History, Transmission cycle, History, Epidemiology, Eradicability, Interventions, Cyclopicide, Water supply, Health education, Community-based surveillance, Evaluation results, Sensitivity of surveillance, Ghana's poor performance, The next phase, Case containment, Integrated surveillance